Primary uterine broad ligament ependymoma with CHEK2p.H371Y germline mutation: A CARE‐compliant case report uterine broad ligament ependymoma. Issue 1 (30th October 2021) - Yin, Jiaxin; Yao, Min; Lu, Hongdi; Cong, Xiaofeng; Cui, Pengfei; Liu, Ziling
Abstract: Ependymomas arise from ependymal cells lining the ventricles and central canal of the spinal cord and can occur throughout the whole neuraxis. The lesion rarely occurs in extracranial or extraspinal regions, particularly in the uterine broad ligament. Thus, for the pathogenesis of nonsacral extra‐central nervous system (CNS) ependymomas remains elusive. Here, we describe a rare case of primary uterine broad ligament. ependymoma with cell‐cycle‐checkpoint kinase 2 ( CHEK2 ) p.H371Y germline mutation. A 45‐year‐old woman presented with a uterine mass. The transvaginal sonographic examination confirmed a 4.4 cm × 3.7 cm, cystic and solid, mass located on the right side uterine wall near isthmus. First, laparoscopy with the neoplasm resection was carried out. Based on morphological and immunohistochemical characteristics of tumor cells that expressed glial fibrillary acidic protein ( GFAP ), S‐100, and vimentin, the tumor was diagnosed as an ependymoma. After that, she underwent a laparotomic total hysterectomy, bilateral salpingo‐oophorectomy, and lymphadenectomy. Furthermore, we performed next‐generation sequencing (NGS) of the patient's resected tumor tissue and peripheral blood and identified a novel CHEK2 p.H371Y germline mutation. Following surgery, the patient received oral tamoxifen (10 mg 2/day) and followed by letrozole (2.5 mg/day) for 6 months. The patient remained disease‐free after 4 years of follow‐up. Conceivably, CHEK2 p.H371Y is a driving gene for the development of extra‐CNS ependymoma.